2018
DOI: 10.1038/s41598-018-33950-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of macaque microbiota compared to the human counterparts

Abstract: Studies on the microbial communities in non-human primate hosts provide unique insights in both evolution and function of microbes related to human health and diseases. Using 16S rRNA gene amplicon profiling, we examined the oral, anal and vaginal microbiota in a group of non-captive rhesus macaques (N = 116) and compared the compositions with the healthy communities from Human Microbiome Project. The macaque microbiota was dominated by Bacteroidetes, Firmicutes and Proteobacteria; however, there were marked d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 78 publications
(79 reference statements)
12
43
0
Order By: Relevance
“…Yatsunenko et al reported that observed OTUs increased with age in all three populations [12]. In a recent study of non-captive rhesus macaques Chen et al reported that male adults had significant higher Shannon index than male juvenile [27]. However, under a well-controlled environment provided by captivity, alpha diversity changes are probably smoothed out.…”
Section: Discussionmentioning
confidence: 99%
“…Yatsunenko et al reported that observed OTUs increased with age in all three populations [12]. In a recent study of non-captive rhesus macaques Chen et al reported that male adults had significant higher Shannon index than male juvenile [27]. However, under a well-controlled environment provided by captivity, alpha diversity changes are probably smoothed out.…”
Section: Discussionmentioning
confidence: 99%
“…In our male animals, notable urethral taxa include Prevotella , Porphyromona , and Ezakiella , have all been previously associated with the urinary tract microbiome of adult men ( 2325 ). Prevotella has been previously detected in the genital microbiome of healthy female rhesus monkeys indicating that this genus plays a residential role in the rhesus monkeys genital microbiome ( 10 ). In humans, some species of Prevotella have been associated with disease states (e.g., bacterial vaginosis ( 26 )) while other species can be found in clinically healthy women (e.g., post-partum, ( 21 )).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have laid the groundwork in characterizing the genital microenvironment of various species of captive and wild NHPs ( 2, 1012 ). Unlike the vaginal microbiome of humans, which is often dominated by a single Lactobacillus species ( 13 ), NHPs, including rhesus monkeys, harbor a diverse set of vaginal microbes ( 2, 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the genetic relatedness of primates, and hence greater physiological and microbiological similarity to humans, requires less interpolation compared to other animal model systems [28][29][30][31]. Mice are a common experimental model system used in preclinical studies of human drugs and vaccines.…”
Section: Study Rationalementioning
confidence: 99%
“…However, the NHP model is better suited to answering key questions about Bt OMV vaccine efficacy and safety in humans. This is because the genetic relatedness of primates, and hence greater physiological and microbiological similarity to humans, requires less interpolation compared to other animal model systems [28][29][30][31]. Therefore, the use of NHPs de-risks the development pathway for Bt-OMV vaccine by providing assurance that the NHP microbiome and histological integrity of the GI tract, and other associated tissues, are not adversely affected following immunization.…”
Section: Study Rationalementioning
confidence: 99%